The Relationship between Coffee Consuming Habits and Blood Pressure in the Elderly in the Pariaman Community Health Center Working Area - Arini, Larusuci; Syarli, Setiadi; Rahmadeni, Asfri Sri; Widya, Fitra (Universitas Pahlawan Tuanku Tambusai, 2024)
Increasing age in the elderly affects the performance of the cardiovascular system, one of which is the problem of high blood pressure. However, high blood pressure in the elderly is also influenced by various other factors, including genetics, physical activity, nutrition, and lifestyle or habits. This study focused on examining the habitual factors of the elderly in terms of coffee consumption and its relationship with the elderly's blood pressure. The research method uses quantitative descriptive-analytical research principles with a cross-sectional study approach. This study targets a population of 268 elderly people in the Pariaman Community Health Center (Pauh Barat) Work Area. The research sample involved 83 elderly respondents. Analyze statistical data and use the chi-square formula. The results of this study show that there is a significant relationship between the habit of consuming coffee and blood pressure in the elderly at a significance level of P = 0.010 (< ? 0.05). From the results of this research, it can be concluded that the prognosis for cardiovascular disorders such as hypertension in the elderly can be supported through efforts to improve behavior by reducing the habit of drinking excessive coffee. Research suggests that support from health workers and those closest to the elderly is needed to provide education and understanding in controlling the excessive coffee habit of the elderly so that the normal aging process experienced by the elderly is not exacerbated by habits that can disrupt health.